Uma leitura histórico-social do abandono em O sino e a rosa, de Alina Paim - Oliveira, Michelle Pereira de (2019)
The practice of child abandonment dates back to ancient times, and for many years children were considered as being inferior to adults since their vulnerability would turn them in one of the main victims of mortality, which in a certain way led many families to a recurrent predisposition to let go of them. Concerning Brazil, child abandonment is one of many other social problems that persevere until nowadays, which contrasts with the title “developing country” (given its economic potential). Considering these aspects, the present research sought to trace a historical and social portrait of abandonment, having as object the text “O sino e a rosa” (1965) by the Brazilian writer Alina Paim. We seek to establish a dialogue between literature and society, starting from the assumption that literature is an instrument of self-consciousness and criticism to man and, in this way, we conceive Art as a mechanism that clarifies our overview on social problems, helping us to reflect, question and position ourselves on this kind of issues. Thus, we understand that the mentioned Mrs. Paim’s text reveals the issue of child abandonment when reporting the pain suffered by the character Catherine – a girl left in a baby hatch and supported by a religious institution. For this understanding, the following authors have served as theoretical contributions: J. Derrida (2014), M. Foucault (1996), F. Engels (1984), O. Ianni (1999), M. Priori (1996), G. Bachelard (1979), among others; besides A. Bosi (1995) and A. Candido (2006) who illuminated the perspective adopted in this work.